Determination of autoregressive coefficients using Complex-Valued Neural Network - Aibinu, Abiodun Musa; Salami, Momoh Jimoh Emiyoka; Shafie, Amir Akramin (2009)
This paper discusses a new approach for Complex Autoregressive(CAR) model parameter estimation using Complex-Valued Neural Network (CVNN) technique. The CAR coefficients are computed from the adaptive weights and linear coefficients of the multi layer CVNN. The performance of the proposed technique has been evaluated using simulated Complex-Valued Data (CVD) with three different types of linear activation functions. The results show that the proposed method can accurately determine CAR coefficients for a properly trained CVNN.